Coefficient of variation on Gd-EOB MR imaging: Correlation with the presence of early-stage hepatocellular carcinoma in patients with chronic hepatitis B. Issue 102 (May 2018) - Lee, Jung Hun; Kim, Youe Ree; Lee, Guy Mok; Ryu, Jong Hyun; Cho, Eun Young; Lee, Young Hwan; Yoon, Kwon-Ha
Abstract: Purpose: To study whether the measurement of hepatic fibrosis on gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) magnetic resonance (MR) imaging using the coefficient of variation (CV) might be correlated with the presence of hepatocellular carcinoma (HCC) in patients with chronic hepatitis B (CHB). Materials and methods: This study included 104 patients with and without CHB, who were divided into 4 groups: control group, CHB without liver cirrhosis (LC; Group I), CHB with LC (Group II), and CHB with LC and HCC (Group III). MR images were analyzed to measure the inhomogeneity of signal intensities calculated using the CV map of the liver parenchyma. Intergroup comparisons of CV values were performed using ANOVA. The diagnostic performance of the CV map and alpha-fetoprotein (AFP) for diagnosing HCC was evaluated using the receiver operating characteristic (ROC) curve. Results: On the hepatobiliary phase of Gd-EOB-DTPA-enhanced T1-weighted imaging, the mean CV values of the control group and Groups I, II, and III were 3.9 ± 0.99, 3.97 ± 1.09, 5.58 ± 2.05, and 6.80 ± 2.34, respectively ( P = 0.000). On ROC analysis of the CV value for predicting HCC, the value of the area under the curve (AUC) on Gd-EOB-DTPA MR imaging was 0.788 (95% CI: 0.697-0.862). The sensitivity and specificity were 84.2% and 63.6%, respectively, at a CV cutoff value >4.75. The value of AUC determined using AFP was 0.766. Conclusion: The CV value for hepatic fibrosis on Gd-EOB-DTPA MR imaging may be correlated with the presence of HCC in patients with CHB, and shows comparable diagnostic performance to AFP analysis.